Madrasah Development and Governance in Ma’had Tawi-Tawi: Institutional Policies and Governmental Transitions Over Time - Rudyn Samaruddin Alaldaya; Abd Madjid; Muhammad Hisyam Syafii (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2026)
Research on Islamic education in the Philippines has primarily focused on conflict resolution and curriculum integration. At the same time, limited attention has been given to the evolution of institutional governance amid political transitions, particularly in peripheral Muslim-majority regions such as Tawi-Tawi. This study addresses this gap by examining the historical development and governance of Ma’had Tawi-Tawi, the first Islamic educational institution in the province, within the broader framework of national education policy and political transformation. Employing a Systematic Review and Bibliometric Analysis, this research maps global scholarly discourse on madrasa development, governance, and policy alignment. From 600 Scopus-indexed articles published between 2015 and 2025, 90 relevant studies were selected based on peer-review status, English language, and thematic relevance, and analyzed using VOSviewer. The analysis identified four dominant thematic clusters: policy impact, historical development, governance transitions, and leadership dynamics. The findings indicate that Ma’had Tawi-Tawi’s sustainability is closely linked to adaptive leadership and its ability to integrate Islamic educational traditions with national curriculum standards. Nevertheless, constitutional constraints related to the separation of church and state continue to limit direct government funding for religious schools. The Bangsamoro Organic Law, however, provides greater institutional resilience through regional autonomy and legal recognition. Policy recommendations include strengthening intergovernmental coordination, enhancing teacher capacity, and formalizing the integration of curriculum. Future studies should explore comparative governance models across the Bangsamoro region to inform sustainable Islamic education policies.